Smart City: The state of the art, definitions, characteristics and dimensions - Vasudavan H.; Gunasekaran S.S.; Balakrishnan S. (American Scientific Publishers, 2023)
The notion of smart city embrace from urbanization with the unceasing boom of population in a city. The rising population in cities require high demand on living standard, facilities and social sustainability, in fact, it is challenging for the existing scarce resources and services to complement the citizen's needs and demand. Thus, the model of smart city emerges as a solution to strategically integrate people, process, data and computing technology. Technologies such as Internet of Things, Big Data and Cloud Computing can be integrated with physical infrastructure to support efficient resourceful services and assure sustainable living standard for the citizens. To transform a city into a smart city it involves a complex and multidimensional process which rapidly changes according to the citizen's needs. Conversely, there is a lack of universal standard route in being smart and various cities has implemented many methods in understanding a smart city. This paper aims to produce a systematic research to comprehend the fundamental concept of smart city's characteristics and dimensions. This research presents various literature definitions of smart cities, followed by commonly discussed smart city characteristics and dimensions. Copyright 2019 American Scientific Publishers All rights reserved.